Implementasi Evaluasi Formatif untuk Penilaian Ranah Afektif Siswa dalam Pembelajaran IPA di Sekolah Dasar - Nina Husna; Hendro Prasetyono (STKIP HARAPAN BIMA, 2026)
This study aims to describe the implementation of formative evaluation in assessing the affective domain of students in science learning at elementary schools. Affective domain assessment plays an important role in shaping students' character, such as discipline, responsibility, cooperation, and honesty. However, the implementation of affective assessment in elementary schools still faces various obstacles, especially in the observation process and the objectivity of the assessment. Therefore, this study was conducted to determine the implementation of formative evaluation, the obstacles faced by teachers, and the efforts made in assessing students' affective domain. This study used a qualitative descriptive method. The research subjects consisted of elementary school teachers and students. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of formative evaluation in the affective domain has been carried out through observation of students' attitudes during the learning process. Formative evaluation has a positive impact on students' character development, such as increased discipline, responsibility, and cooperation. However, the implementation of the assessment still faces obstacles. To overcome these obstacles, teachers use assessment rubrics and work together with parents to monitor the development of students' attitudes.